A Case of Meconium Aspiration Syndrome in a Bottlenose Dolphin (Tursiops truncatus) Calf - TANAKA, Miyuu (The Japanese Society of Veterinary Science, 2013)
Stillbirth and neonatal mortality are significant problems in captive breeding of dolphins, however, the causes of these problems are not fully understood. Here, we report a case of meconium aspiration syndrome (MAS) in a male neonate of bottlenose dolphin (Tursiops truncates) who died immediately after birth. At necropsy, a true knot was found in the umbilical cord. The lungs showed diffuse intraalveolar edema, hyperemic congestion and atelectasis due to meconium aspiration with mild inflammatory cell infiltration. Although the exact cause of MAS in this case was unknown, fetal hypoxia due possibly to the umbilical knot might have been associated with MAS, which is the first report in dolphins. MAS due to perinatal asphyxia should be taken into account as a possible cause of neonatal mortality and stillbirth of dolphin calves.